2021
DOI: 10.1038/s41467-021-25724-y
|View full text |Cite
|
Sign up to set email alerts
|

MAD2L2 dimerization and TRIP13 control shieldin activity in DNA repair

Abstract: MAD2L2 (REV7) plays an important role in DNA double-strand break repair. As a member of the shieldin complex, consisting of MAD2L2, SHLD1, SHLD2 and SHLD3, it controls DNA repair pathway choice by counteracting DNA end-resection. Here we investigated the requirements for shieldin complex assembly and activity. Besides a dimerization-surface, HORMA-domain protein MAD2L2 has the extraordinary ability to wrap its C-terminus around SHLD3, likely creating a very stable complex. We show that appropriate function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…This model is consistent with previous work suggesting that 53BP1 acts primarily to ensure the fidelity of DSB repair 24 , 67 . In this view, the dynamic nature of SHLD complex assembly and disassembly would be an important parameter to allow for multiple DSB repair machineries to accurately process and join DSB ends 56 , 68 , 69 . The nature of the alt-NHEJ pathway acting during CSR remains to be fully established 10 , 11 , 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This model is consistent with previous work suggesting that 53BP1 acts primarily to ensure the fidelity of DSB repair 24 , 67 . In this view, the dynamic nature of SHLD complex assembly and disassembly would be an important parameter to allow for multiple DSB repair machineries to accurately process and join DSB ends 56 , 68 , 69 . The nature of the alt-NHEJ pathway acting during CSR remains to be fully established 10 , 11 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that DSB end protection might in fact play a limited role in the ability of 53BP1 to support CSR, based on the observation that a mutant form of 53BP1 defective for RIF1 recruitment still supports robust CSR 55 . Yet, B cells deficient for any component of the SHLD complex as well as for RIF1 display defective CSR [27][28][29][30][31][32][33][34][56][57][58] . The recent identification of distinct modes of RIF1 and SHLD recruitment at DSBs and action to promote DNA repair might partially explain this discrepancy 59 .…”
Section: Discussionmentioning
confidence: 99%
“…This slow, but spontaneous, conversion is a rate-limiting step in the assembly of the respective effector complex. Indeed, we previously showed that REV7-SHLD3 complex formation takes several hours (de Krijger et al, 2021). However, as described in Figure 3b, the purified REV7 is already in the ‘closed’ state, so potentially no conversion would be necessary.…”
Section: Resultsmentioning
confidence: 99%
“…Central to the unusual interaction mechanism of REV7 is the extraordinary ability to wrap its C-terminal tail (‘seat-belt’) around an interacting peptide motif of a client protein, thereby creating a very stable complex. Both Polζ and Shieldin incorporate a dimer of REV7 molecules, which are essential for their function in vitro and in cells (de Krijger et al, 2021; Malik et al, 2020; Rizzo et al, 2018). Using the seat-belt mechanism, REV7 captures the REV7-binding-motifs (RBM) in SHLD3 (residues 49 to 62) and REV3 (RBM1, residues 1875 to 1896, and RBM2, residues 1991 to 2012) (Dai et al, 2020; Hara et al, 2010; Rizzo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of MAD2L2 (also known as MAD2B or REV7 ) decreases DNA end resection, which increases NHEJ and chromosomal abnormalities, resulting mitotic catastrophe in PARP inhibitor treated HR-proficient cells. In addition, MAD2L2 can also inhibit end-resection in irradiation (IR)-induced DNA double-strand breaks (DSBs) ( Boersma et al, 2015 ; Simonetta et al, 2018 ; De Krijger et al, 2021 ). MAD2L2 accelerates end-joining of DNA double-strand breaks in several settings, including immunoglobulin class switch recombination through ATM kinase activity ( Xu et al, 2015 ; Batenburg et al, 2017 ; Noordermeer et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%